Effects of subacute ingestion of chlorogenic acids on sleep architecture and energy metabolism through activity of the autonomic nervous system: a randomised, placebo-controlled, double-blinded cross-over trial. Issue 7 (17th April 2017) - Park, Insung; Ochiai, Ryuji; Ogata, Hitomi; Kayaba, Momoko; Hari, Sayaka; Hibi, Masanobu; Katsuragi, Yoshihisa; Satoh, Makoto; Tokuyama, Kumpei
Abstract: Chlorogenic acids (CGA) are the most abundant polyphenols in coffee. Continuous consumption of CGA reduces body fat and body weight. Since energy metabolism and sleep are controlled by common regulatory factors, consumption of CGA might modulate sleep. Lack of sleep has been identified as a risk factor for obesity, hypertension and type 2 diabetes. The aim of this study was to determine the effects of ingesting CGA over 5 d on energy metabolism and sleep quality in humans. A total of nine healthy subjects (four male and five female) completed a placebo-controlled, double-blinded, cross-over intervention study. Subjects consumed a test beverage containing 0 or 600 mg of CGA for 5 d. On the fifth night, subjects stayed in a whole-room metabolic chamber to measure energy metabolism; sleep was evaluated using polysomnographic recording. It was found that CGA shortened sleep latency (9 (sem 2) v . 16 (sem 4) min, P <0·05) compared with the control, whereas no effect on sleep architecture, such as slow-wave sleep, rapid eye movement or waking after sleep onset, was observed. Indirect calorimetry revealed that consumption of CGA increased fat oxidation (510 (sem 84) kJ/8 h (122 (sem 20) kcal/8 h) v . 331 (sem 79) kJ/8 h (81 (sem 19) kcal/8 h), P <0·05) but did not affect energy expenditure during sleep. Consumption of CGA enhanced parasympathetic activity assessed from heart-rate variability during sleep (999 (sem 77) v . 919 (sem 54), P <0·05). A period of 5-d CGA consumption significantly increased fat oxidation during sleep, suggesting that beverages containing CGA may be beneficial to reduce body fat and prevent obesity. Consumption of CGA shortened sleep latency and did not adversely affect sleep quality.